2014
DOI: 10.1063/1.4862907
|View full text |Cite
|
Sign up to set email alerts
|

First principles molecular dynamics without self-consistent field optimization

Abstract: We present a first principles molecular dynamics approach that is based on time-reversible extended Lagrangian Born-Oppenheimer molecular dynamics [A. M. N. Niklasson, Phys. Rev. Lett. 100, 123004 (2008)] in the limit of vanishing self-consistent field optimization. The optimization-free dynamics keeps the computational cost to a minimum and typically provides molecular trajectories that closely follow the exact Born-Oppenheimer potential energy surface. Only one single diagonalization and Hamiltonian (or Fock… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…It is easy to see that previous formulations of extended Lagrangian Born-Oppenheimer molecular dynamics in the limit of vanishing self-consistent field optimization [17,23,24] are recovered with a scaled δ-function approximation of the kernel, i.e. for K(r, r ′ ) = −c δ(r − r ′ ) in Eq.…”
Section: E Stabilitymentioning
confidence: 99%
“…It is easy to see that previous formulations of extended Lagrangian Born-Oppenheimer molecular dynamics in the limit of vanishing self-consistent field optimization [17,23,24] are recovered with a scaled δ-function approximation of the kernel, i.e. for K(r, r ′ ) = −c δ(r − r ′ ) in Eq.…”
Section: E Stabilitymentioning
confidence: 99%
“…With this method, the time reversibility of the electronic structure is maintained and the stability of the BOMD simulations is greatly improved. 6,31,32) Recently, we have combined this XL-BOMD scheme with the DMM method and demonstrated that the combined method enables us to perform efficient and reliable FPMD simulations with the OðNÞ method. 7) The Lagrangian in the XL-BOMD scheme L XBO is defined as follows, using the Lagrangian in the usual BOMD method L BO ,…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the fluctuations of the total energy during a microcanonical molecular dynamics simulation of liquid water that was performed using LATTE 58 and the extended Lagrangian formulation of Born-Oppenheimer molecular dynamics. 50,[67][68][69][70] The density matrix was calculated from a partitioning over separate subgraphs of S τ (t), with one water molecule per core. For the Fermi-operator expansion (at zero temperature) we used the recursive SP2 algorithm.…”
Section: B Molecular Dynamics Simulationmentioning
confidence: 99%